Application of Edge Preserving and Interpolation Algorithm Based on Wavelet Transformation in Mechanical Inspection and Flaw Detection. (October 2019) - Xie, Qi; Zhang, Ying; Ru, Lina; Luo, Hongfei; Cui, Qingbin
Abstract: In mechanical inspection and flaw detection, the fault point in the image is often small, it is easy to cause the occurrence of missed detection, and due to the internal factors of the imaging system and environmental effects, the final image is often degraded, which is manifested as the deterioration of subjective vision and the decrease of actual resolution. In order to improve the resolution of the image without changing the existing imaging system and prevent the occurrence of the phenomenon of missed detection. An interpolation edge preserving algorithm based on wavelet transformation is proposed, the algorithm firstly performs edge detection and interpolation for low-resolution image, after that, the initial interpolated magnified image was decomposed by wavelet, and the low-frequency component image after wavelet decomposition was replaced by the original low-resolution image. Then, the inverse wavelet transform was carried out to obtain the high-resolution image with good edge information. The experimental results showed that compared with the traditional interpolation method and wavelet interpolation method, this algorithm performs better in the edge visual effect and objective index, and it is an effective algorithm to improve the resolution of detection image.